The role of RNA uptake in platelet heterogeneity - Clancy, Lauren; Beaulieu, Lea M.; Tanriverdi, Kahraman; Freedman, Jane E. (Thrombosis and Haemostasis, 2017)
The role of platelets in regulating vascular homeostasis has expanded beyond mediation of haemostasis and thrombosis. The discovery of platelet RNA and the presence of subpopulations of platelets containing varying amounts of RNA suggest a role for platelet transcripts in vascular function. As the RNA in anucleated platelets is biologically functional and may transfer to other vascular cells, we hypothesised that platelet RNA diminishes over the lifespan of the platelet with diminishing platelet size due to horizontal cellular transfer. The purpose of this study is to determine if platelet RNA variance is the result of horizontal cellular transfer between platelets and other vascular cells. Utilising platelet sorting and RNA sequencing, we found that smaller platelets contained a more diverse set of transcripts than larger platelets. Further investigation using fluorescence imaging, gene expression analyses and in vitro and in vivo modelling revealed that platelets take up RNA from other vascular cells in a complex manner, revealing a dynamic role for platelets in modulating vascular homeostasis through bidirectional RNA transfer. The resultant RNA profile heterogeneity suggests unique functional roles for platelets dependent on size and complexity. This study expands our basic understanding of platelet function and heterogeneity and is the first to evaluate endogenous vascular RNA uptake and its relation to platelet processes. Our findings describe a novel endogenous phenomenon that can help elucidate the platelet’s role in these non-thrombotic and haemostatic fields, as well as present potential for diagnostic and therapeutic development.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Platelets; platelet physiology; RNA transfer; RNA uptake